Radiocarbon and Luminescence Dating of Lacustrine Sediments in Zhari Namco, Southern Tibetan Plateau - Cong, Lu; Wang, Yixuan; Zhang, Xiying; Chen, Tianyuan; Gao, Donglin; An, Fuyuan (Frontiers in Earth Science, 2021)
There are more than 1,000 lakes within the Tibetan Plateau (TP), all of which are sensitive to changes in regional climate and local hydrology. Lacustrine sediments within these lakes preserve a good record of these changes. However, determining their precise ages is difficult due to the complex nature of lake reservoir effects (LRE), which limit our understanding of paleoenvironmental changes. Focusing on an exposed 600 cm thick lacustrine sediment profile located in western Zhari Namco, we used a combination of both radiocarbon and optically stimulated luminescence (OSL) dating methods in order to evaluate the carbon reservoirs of bulk organic matter (BOM) and aquatic plant remnants (APR), and to explore the age differences between 14C and OSL and their respective reliability. We demonstrated that (i) OSL ages were changed in stratigraphic order, and the OSL age just below the beach gravel layer was consistent with previously reported paleoshoreline ages; (ii) 14C ages were divergent between BOM and grass leaves; (iii) 14C ages of BOM were older than 14C ages of APR; and (iv) all 14C ages were older than OSL ages. This could be attributed to changing LRE in the past, causing the 14C ages to appear unstable during the deposition period. Although the 14C ages of terrestrial plant remnants (TPR) were not affected by LRE, an analyzed twig nonetheless returned a 14C age older than its respective layer’s OSL age, suggesting it may have been preserved on land prior to transportation into the lake. Our study suggests that OSL ages are more reliable than 14C ages with respect to Zhari Namco lacustrine sediments. We recommend caution when interpreting paleoenvironmental changes based on lacustrine sediment 14C ages alone.